Supplement tо clinic-practical recommendations “Chronic diseases of veins of the lower extremities and pelvis” - Editorial Board (Клінічна хірургія)
Supplement tо clinic-practical recommendations “Chronic diseases of veins of the lower extremities and pelvis”